2023
DOI: 10.1111/psyp.14261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of respiratory phases on the processing of emotional and non‐emotional visual stimuli

Abstract: Internal bodily signals are known to impact brain functions. Interoception-the processing of internal bodily signals by the nervous system (Khalsa et al., 2018)-is associated with physical and mental health (Schulz & Vögele, 2015) and emotion ). An increasing number of recent studies has focused on the effect of the respiratory phase-an internal bodily signal-on the perceptual and cognitive processing of external events (e.g., Mizuhara & Nittono, 2022;Perl et al., 2019;Zelano et al., 2016). The present registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…For example, task‐irrelevant visual information can be more inhibited during systole than diastole (Pramme et al., 2014, 2016). Emotional facial expressions were detected better (Azevedo et al., 2018; Garfinkel et al., 2014; Mizuhara & Nittono, 2023) and perceived more intensely (Garfinkel et al., 2014; Leganes‐Fonteneau et al., 2021) at systole than diastole. Feedback information processing associated with monetary gain and loss was also greater at systole than diastole (Kimura, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, task‐irrelevant visual information can be more inhibited during systole than diastole (Pramme et al., 2014, 2016). Emotional facial expressions were detected better (Azevedo et al., 2018; Garfinkel et al., 2014; Mizuhara & Nittono, 2023) and perceived more intensely (Garfinkel et al., 2014; Leganes‐Fonteneau et al., 2021) at systole than diastole. Feedback information processing associated with monetary gain and loss was also greater at systole than diastole (Kimura, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The recording settings were identical to those used in our previous study (Mizuhara & Nittono, 2023), except that the reference electrode was placed at the nose tip. Biosignals were recorded using an ActiveTwo system (BioSemi, Amsterdam, Netherlands) with a bandpass filter of 0-400 Hz and a sampling rate of 2048 Hz.…”
Section: Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, investigations into the effect of breathing on perception and emotion have yielded inconsistent findings. For example, some studies have reported effects of breathing phase on emotion processing and perception (Kluger et al., 2021; Mizuhara & Nittono, 2023; Zelano et al., 2016), while others have not (Johannknecht & Kayser, 2022; Mizuhara & Nittono, 2022). One reason for these mixed results may be the utilization of diverse technical and statistical methodologies for identifying variations in behavioral performance throughout the respiratory cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that inspiration increases the speed of emotional processing (Zelano et al, 2016), and that participants make more volitional movements during expiration (Park et al, 2020). These and many more recent reports suggest that respiratory rhythms play a fundamental role in shaping exteroceptive, affective (Bagur et al, 2021;Mizuhara & Nittono, 2023;Zelano et al, 2016), and cognitive behaviour (for reviews, see Allen et al, 2022;Azzalini et al, 2019;Braendholt et al, 2023;Heck et al, 2022).…”
Section: Introductionmentioning
confidence: 94%